PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH DALAM MENGEMBANGKAN KETERAMPILAN BERPIKIR KRITIS PADA PEMBELAJARAN SOSIOLOGI - Pingky, Maria Chintya; Zakso, Amrazi; Rustiyarso, Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:This thesis entitled "Application of Problem Based Learning Model in Developing Critical Thinking Skills on Sociology Learning In Class X IIS 1 State Senior High School 9 Pontianak". The research method used in this research is Experiments with Quasi Experimental research form and Post-test design only group design. The results of this study: 1) Based on the pre-test results after divided between mean value (average) 55.45 with standard deviation 5.602. This indicates that the pres-test results are normally distributed. If both data are normal then t test will be performed, based on t test with ? = 0,05 level in the experimental class and control class on the sig (2-tailed) 0,000 column, there is no significant difference in the pre-test result, so it can be said that the experimental class and the control class have the same ability. 2) Based on the post test resulted the average value of 65.61 standard deviation yield value 9.772. If the value of skewness tastes between values 2 to +2 then the data is said to be normal.Keyword : Problem-Based Learning, Critical Thinking.